Black hole sun - Gill, David Macinnis (Greenwillow Books, 2010)
On the planet Mars, sixteen-year-old Durango and his crew of mercenaries are hired by the settlers of a mining community to protect their most valuable resource from a feral band of marauders
Keywords: Science fiction; Mars (Planet) / Fiction; Mars (Planet) / Juvenile fiction